IKHLAS DALAM BERIBADAH SESUAI TUNTUNAN AL-QUR’AN DAN HADITS - Sulman Sulman; Nur Alim Hamzah (Jurnal Ushuluddin Adab dan Dakwah, 2019)
Worship is a form of devotion of a servant to his God based on sincerity and submission. The purpose of worship is to obtain the pleasure of Allah, alone. Ikhlas is when we make intentions in doing a deed only because of Allah alone, do it not because other than Allah. Sincere is really and clean heart (really out of a pure heart), honest, not pretend, not serong, sincere, sincere. Perfect sincerity towards something is our sincerity in being mentally good continuously (istiqomah). Sincerity in worship has positive implications for everyday life. The state of a clean, pure, and pure heart of bad things strongly supports us to carry out various positive activities in order to pick up His pleasure.